Advancements in Timber–Steel Hybridisation: A Review on Techniques, Applications, and Structural Performances - Abdulaziz Abdulmalik; Benoit P. Gilbert; Hong Guan; Tuan Ngo; Alex Remennikov (Buildings, 2025)
Timber–steel hybridisation offers a balanced approach by capitalising on the high strength-to-weight ratio and sustainability of the timber while also benefiting from the high stiffness and ductility of the steel, contributing to the improved performance of hybrid structural elements. This paper reviews key aspects of timber–steel hybridisation, with a particular emphasis on the connection methods between timber and steel, including adhesive bonding and mechanical fastening, as well as the different types of reinforcement configurations. In particular, this review covers two main types of adhesives used in timber–steel hybrid systems, namely, epoxy and polyurethane, and two primary types of mechanical fasteners, namely, bolts and screws. The mechanical performances of all hybridisation methods are reviewed. The importance of surface treatments, such as shot blasting for steel and mechanical abrasion for timber, is also discussed as a key factor in optimising adhesive bonds. Furthermore, various reinforcement configurations, including top, bottom, side, and embedded arrangements, are evaluated for their impact on the structural efficiency and fire performance. To support this evaluation, calculations have been carried out to illustrate how different reinforcement configurations influence the stress distribution in timber–steel hybrid beams. By providing detailed insights into these critical aspects, this paper serves as a valuable decision-making tool, offering guidance for researchers and industry professionals for selecting the appropriate bonding techniques and configurations to meet specific structural objectives and advance sustainable construction practices.